Using virtual fieldwork to support interprofessional and community-based learning: students from four faculties investigate life on a remote island in Japan - Yatsushiro, Rika; Matsuda, Fumiyo; Causer, Bo; Inoue, Kazuhiro; Kikata, Junne; Miura, Naoki; Hashimoto, Kumiko; Akasaki, Yasuaki; Unedaya, Keiko (Frontiers in Education, 2024)
Introduction The Mishima Islands in Kagoshima Prefecture, Japan, are remote islands designated as medically underserved. Supporting the people living in such remote islands requires a multifaceted examination of the livelihoods of the residents, including their health, work, and living environment. Methods Students from the faculties of nursing, veterinary science, agriculture, and engineering participated in a 3-day virtual fieldwork session held synchronously from the campus of Kagoshima University and on a remote island in the Mishima Mura island group in Kagoshima Prefecture, Japan. Coursework and post-course surveys were analyzed to determine student engagement and learning. In particular, the analysis considered learning in relation to interprofessional learning and community-based learning. Results and discussion Students expressed being able to conduct fieldwork online, collaborate with students from multiple faculties and graduate schools, and apply their expertise. These outcomes were reflected in the five-point Likert scale evaluation responses, highlighting a sense of accomplishment and satisfaction. Virtual fieldwork can contribute to student learning by introducing new concepts and allowing them to consider development issues in remote areas from multiple perspectives.